Web-Based Online Exam Application for Junior High Schools Case Study: SMP Hasyim Asyari Tulangan) - David Eka Ramadhan; Ika Ratna Indra Astutik (CV. Media Digital Publikasi Indonesia, 2025)
Technological developments have had quite rapid consequences in the field of education, the application of technology in the form of information systems, such as the use of online examination systems can be applied in the field of education. The online exam system is part of the distance learning information system via internet technology. The exams held by most educational institutions (in this case schools) are standardized. Like the exam system implemented at HASYIM ASHARI JUNIOR HIGH SCHOOL which still uses manual methods in data management, especially exam data management. HASYIM ASHARI JUNIOR HIGH SCHOOL really needs an information system at this time. This makes the final assessment contain a subjective element by involving human opinion. The aim of creating an online exam application system is to increase the speed and simplicity of the exam evaluation process. Examiners no longer check individual participant answer sheets and then calculate scores, but the software transfers scores to a database with automatic calculations based on participant answers. The method used in this research is the waterfall method and application testing uses the UAT (User Acceptance Test) method. The result of this research is the creation of a web-based online exam application for junior high schools that can provide assessment results in real time.